2022
DOI: 10.3390/poultry1040023
|View full text |Cite
|
Sign up to set email alerts
|

Variable Effects of the In Ovo Administration of an Escherichia coli Vaccine in the Amnion or Air Cell on Commercial Layer Embryo and Hatchling Development

Abstract: The effects of injecting the Poulvac E. coli vaccine (PECV) into either the air cell (AC) or amnion (AM) at different dosages at 18 days of incubation (DOI) on Hy-Line W-36-layer embryo and hatchling development were investigated. Serial dilutions of the PECV in diluent provided either 6.5 × 104, 6.5 × 103, 6.5 × 102, or 6.5 × 101 CFU dosages of E. coli. A diluent only injection treatment was included as a control. A total of 19 live embryonated eggs in each of 10 treatment groups were represented on each of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…All serial dilutions were performed in sterile Marek's disease commercial diluent (Merial, Inc., Athens, GA), and all titer determinations were determined from duplicate plates and were performed as described by Lindsey et al (2022) . Upon plating the full dose of the PECV, pre- and postinjection titers (CFU/mL) were observed to be 8.8 × 10 9 and 3.4 × 10 9 , respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All serial dilutions were performed in sterile Marek's disease commercial diluent (Merial, Inc., Athens, GA), and all titer determinations were determined from duplicate plates and were performed as described by Lindsey et al (2022) . Upon plating the full dose of the PECV, pre- and postinjection titers (CFU/mL) were observed to be 8.8 × 10 9 and 3.4 × 10 9 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The injection process took a total of 1.5 h to complete. Cross-contamination prevention between treatments was as described by Lindsey et al (2022) . One egg from each tray (6 per treatment) was randomly selected to determine the accuracy of site of injection ( Elliott et al, 2018 ) and embryonic developmental stage ( Avakian, 2006 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel approach in biotechnology is the use of in ovo vaccination, which involves making a small hole in the blunt end of a chicken egg using an obliquely pointed needle and then delivering a small amount of vaccine into the amniotic cavity using a smaller needle [ 174 ]. In ovo administration is a way of delivering the vaccine into the egg to benefit the developing late-stage embryos before the completion of the incubation period [ 175 ]. It is usually performed at a limited time frame of the incubation when the eggs are being transferred from the setter to the hatcher units, giving advantages such as the capability to vaccinate a larger number of eggs, cost-effective, low human errors, and faster and better immune responses [ 176 ].…”
Section: Vaccine Deliverymentioning
confidence: 99%
“…The efficacy of the vaccine and safety of the embryo depends on the sites of the vaccine administration, including the air cell (AC), allantoic sac (AL), amnion/amniotic fluid (AM), embryonic body (EM), and yolk sac [ 178 ] ( Figure 8 ). For example, vaccines administered into the AC and AL generally show low efficacy as compared to those injected into the AM [ 175 ]. Experiments conducted by Alqhtani and colleagues have suggested that the embryonic mortality in the case of vaccine delivered into the AC and AL is lower; however, the development of humoral immunity is not sufficient and is significantly lower as compared to those injected into the AM [ 179 ].…”
Section: Vaccine Deliverymentioning
confidence: 99%